Who is Who in Knowledge Economy in Africa? - Simplice Asongu; Vanessa S. Tchamyou; Paul N. Acha-Anyi (African Governance and Development Institute (AGDI), 2017)
This study assesses the knowledge economy (KE) performance of lagging African countries vis-à-vis their frontier counterparts with regard to the four dimensions of the World Bank's knowledge economy index (KEI). The empirical exercise is for the period 1996-2010. It consists of first establishing leading nations before suggesting policy initiatives that can be implemented by sampled countries depending on identified gaps that are provided with the sigma convergence estimation approach. The following are established frontier knowledge economy countries. (i) For the most part, North African countries are dominant in education. Tunisia is overwhelmingly dominant in 11 of the 15 years, followed by Libya which is a frontier country in two years while Cape Verde and Egypt lead in a single year each. (ii) With the exception of Morocco that is leading in the year 2009, Seychelles is overwhelmingly dominant in ICT. (iii) South Africa also indomitably leads in terms of innovation. (iv) While Botswana and Mauritius share dominance in institutional regime, economic incentives in terms of private domestic credit are most apparent in Angola (8 years), the Democratic Republic of Congo (3 years) and Tanzania, Sierra Leone and Malawi (each leading in one year).
Keywords: O10; O30; O38; O55; O57; 330; Knowledge economy; Benchmarks; Policy syndromes; Catch-up; Africa